Peningkatan pembelajaran IPA melalui pendekatan Contekstual Teaching and Learning (CTL) di kelas VI SDN 45 Jambak Kecamatan Bayang - Suharto Suharto (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
This research originated from the fact in elementary school that learning is often dominated by teachers as a source of information. The problem is caused by the teacher's learning is more delivery by using the lecture method, so that students become passive listeners. The value of learning comprehension of IPA by using the contextual approach in cycle I and cycle II have increased, where the mastery learning cycle, I students with an average of 64% and in the cycle II is 93%. In addition, students have been trained to find out, test it in study groups and then communicate it to other friends. Thus it can be concluded that the learning of science using a contextual approach can improve student learning outcome's class VI SDN 45 Jambak Kecamatan Bayang.